Outcomes and survival following lung transplantation in non-cystic fibrosis bronchiectasis. Issue 1 (14th February 2022) - Jung, Frederick; Riley, Leonard; Lascano, Jorge
Disease-specific outcomes in patients with non-cystic fibrosis bronchiectasis following lung transplantation are not well described. We performed a retrospective analysis to describe outcomes in these patients. Patients with non-cystic fibrosis bronchiectasis who have undergone lung transplantation in the USA were identified using the Organ Procurement and Transplant Network database. Survival data were analysed for the post-lung allocation score period with Kaplan–Meier curves, and a log-rank test was conducted to compare survival data among an age-, sex- and activation date-matched non-cystic fibrosis bronchiectasis cohort. 721 patients with non-cystic fibrosis bronchiectasis were listed for lung transplantation between March 1992 and September 2019. 407 patients received lung transplantation with a median age at listing of 47 years. The Kaplan–Meier survival analysis for lung transplantation recipient non-cystic fibrosis bronchiectasis patients during the post-lung allocation score period at 1, 5 and 10 years was 87%, 53% and 16%, respectively. The median survival time post-lung transplantation is 6.0 years (interquartile range: 2.3–11.9 years), which is similar to an age- and sex-matched cohort (p=0.86). This retrospective analysis demonstrates that median survival after lung transplantation in non-cystic fibrosis bronchiectasis was similar to other lung transplantation recipients over the study period. We suggest that the development of specific criteria for lung transplantation in non-cystic fibrosis bronchiectasis may improve patient selection and benefit a larger group of patients with this therapy. A retrospective analysis using UNOS data showed that median survival post-LT for patients with non-CF bronchiectasis is 6.0 years, which is similar to an age- and sex-matched cohort https://bit.ly/3eSv95p